Pre-lesson assignments and formative assessment strategies with interactive invention instruction on low achievers in physics - Ukoh, Edidiong Enyeneokpon; Onifade, Sunday Adeyemi (Universitas PGRI Kanjuruhan Malang, 2020)
This study examined the impacts of Interactive–Invention Instruction with Pre-Lesson Assignments (PLA) and Weekly Formative Tests Assessment Strategies (WFTAS) on students with low achievement in Physics in Ibadan, Nigeria. Pre-test post-test quasi-experimental research design and ninety Senior Secondary II students participated in the study. Two experimental groups and control were taught using Interactive-invention instruction, in addition, experimental group (1) was exposed to PLA while group (2) was exposed to WFTAS but the control group was only taught with interactive-invention instruction. Physics Achievement Test (r=0.89) and three teachers guides were instru-ments used while analysis of covariance (ANCOVA) was used to analyse the data. The treatments had significant main effect on low achieving students’ achievements in physics (F(2,75) =9.205; p<0.05, partial η2 = 0.197). Low achieving students exposed to the treat-ments obtained a higher post-test mean score of 14.10 for PLA, 16.02 for WFTAS, than those exposed to Interactive-invention instruction only 11.47. It was therefore concluded that the pre-lesson assignments and weekly formative tests assessment strategies improv-ed the performance of low achieving students in physics. It was recommended that teach-ers identify students with low achievement early and inter-twine their chosen instructio-nal strategies with Pre-Lesson Assignment and Weekly Formative Test Assignment.